Penerapan Latihan Menggunakan Dempel (Pemberat Kaki) untuk Meningkatkan Kecepatan Tendangan Sabit pada Atlet Pencak Silat PSHT Rayon Ketuan Jaya Cabang Musi Rawas - Muhammad Ikhsan Maulana; Muhammad Supriyadi; Wawan Syafutra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine whether the application of training using dempel (leg weights) can increase the speed of crescent kicks in pencak silat athletes from the Dewan Ketuan Jaya, Musi Rawas Branch. The method used was a quasi-experimental method. The population in this study was 15 people. Sampling used the total sampling method with 15 participants. Data collection in this study used a crescent kick speed test. Data analysis used SPSS version 23 with the steps of compiling a frequency distribution table, normality test, and paired sample t-test. The calculation results showed an increase in the average pre-test score of 17.60, categorized as